CITIES: Energetic Efficiency, Sustainability; Infrastructures, Energy and the Environment; Mobility and IoT; Governance and Citizenship - Hernández-Callejo, Luis; Alonso Gómez, Víctor; Nesmachnow, Sergio 1974-; Leite, Vicente; Prieto, Javier; Ferreira, Ângela (MDPI, 2021)
This book collects important contributions on smart cities. This book was created in collaboration with the ICSC-CITIES2020, held in San José (Costa Rica) in 2020. This book collects articles on: energetic efficiency and sustainability; infrastructures, energy and the environment; mobility and IoT; governance and citizenship.